Psychometric properties of the Spanish version of the media health literacy questionnaire (MeHLit-SV) - Navas-Echazarreta, Noelia; Juárez-Vela, Raúl; Martínez-Sabater, Antonio; Gea-Caballero, Vicente; Chover-Sierra, Elena; Echaniz-Serrano, Emmanuel; Ruiz de Viñaspre-Hernández, Regina; Jodrá-Esteban, Blanca; Sánchez-Conde, Pilar; Fernández-Rodrigo, María Teresa; Rodríguez-Calvo, Antonio; Satústegui-Dordá, Pedro José (Frontiers in Public Health, 2024)
Introduction Media health literacy emerges as a response to the vast array of informational disorders prevalent in media communications. Given the absence of a measurement tool for this type of literacy in Spanish-speaking communities, the aim of the present study is to conduct a cross-cultural adaptation of the Media Health Literacy (MeHLit) questionnaire into Spanish and to analyze its psychometric properties in a sample of nursing students. Methods The Spanish version of the MeHLit questionnaire (MeHLit-SV) was obtained through a process involving translation, back-translation, evaluation of the proposed items by a group of 22 experts, and a pilot study with 80 Spanish nursing students. Content validity was assessed using each item’s content validity index (CVI) and Aiken’s V (VdA), while internal consistency was evaluated through Cronbach’s Alpha. Results Following the translation and adaptation process, the final version of the MeHLit-SV comprised 21 items organized into five dimensions. The CVI values exceeded 0.82 for all items, and the overall content validity index (S-CVI) was 0.9. Furthermore, the results of Aiken’s V surpassed the threshold considered acceptable (0.70). After piloting, the questionnaire demonstrated high internal consistency with a Cronbach’s alpha value of 0.936. Conclusion The findings of this research support the reliability and validity of the MeHLit-SV for use among nursing students to measure their level of media health literacy. This questionnaire, with satisfactory psychometric properties and ease of administration, is an useful tool for assessing whether individuals possess the necessary skills to accurately analyze health information they encounter on a daily basis.